Effect of non-genetic factors and body condition score on udder health and milk composition traits of Rathi cattle (Indian Journal of Animal Production and Management, 2024)
The present study was conducted to understand the effect of various non-genetic factors on udder health  and the correlation of Body Condition Score (BCS) with milk composition traits of Rathi cows maintained  at Livestock Research Station (LRS), College of Veterinary and Animal Science, PGIVER, RAJUVAS,  Bikaner, Rajasthan. Milk samples from 50 Rathi cows were collected and analyzed for milk composition  parameters and Somatic Cell count. BCS of each animal was measured. Data regarding parity and stage  of lactation were collected from the record register maintained at farm. The parity reflected a significant  (P0.05) effect on the  Log10 SCC. Except fat percent, all other constituents (i.e. protein, SNF, lactose, density and freezing pint)  were positively correlated (P< 0.05) with BCS.
Keywords: Milk composition; Rathi cows; SCC and Non-Genetic factors